Komunikasi Dialogis Guru dan Orangtua dalam Mendampingi Pembelajaran Jarak Jauh di Masa Pandemi Covid-19 - Carlolus Borromeus Mulyatno; Antonius Wahyu Pradana (ijd-demos, 2022)
AbstractDialogic communication is an important climate and experience in the learning process. The big obstacle in developing dialogic communication is the lack of focus, direction and goals that have been determined together from the start. Openness and cooperation of two parties in designing focus, direction and goals are very important. By using a qualitative approach and a focus group discussion (FGD) method, this study aims to describe the dialogic communication between teachers and parents of the Mangunan Experimental Junior High School (SMPE) in assisting children during the COVID-19 period. Paulo Freire's thoughts on dialogical communication became the analytical framework for the data found. There are three important points found in this study. First, the teachers designed a communication theme with parents that focused on the process of developing children's talents and finding a learning model that allows children to actively explore, be creative and develop themselves integrally. Second, in an intensive dialogical communication process, solutions were found to various problems faced by children. Third, the dialogue between teachers and parents resulted in many important findings related to child development and recommendations for future assistance.Keywords: creation, exploration, self development, talent AbstrakKomunikasi dialogis adalah iklim dan dan pengalaman yang penting dalam proses pembelajaran. Hambatan besar dalam membangun komunikasi dialogis adalah kurangnya fokus, arah dan tujuan yang sejak awal ditentukan bersama. Keterbukaan dan kerjasama dua pihak dalam merancang fokus, arah dan tujuan sangat penting. Dengan menggunakan pendekatan kualitatif dan metode focus group discussion (FGD), penelitian ini bertujuan untuk memotret komunikasi dialogis guru dan orangtua murid Sekolah Menengan Pertama Eksperimental (SMPE) Mangunan dalam mendampingi anak pada masa covid-19.  Pemikiran Paulo Freire tentang komunikasi dialogis menjadi kerangka analisis terhadap data-data yang ditemukan.  Ada tiga poin penting yang ditemukan dalam penelitian ini. Pertama, para guru merancang tema komunikasi dengan orangtua yang berfokus pada proses pengembangan bakat-bakat anak dan menemukan model pembelajaran yang memungkinkan anak secara aktif bereksplorasi, berkreasi dengan mengembangkan diri secera integral. Kedua, dalam proses komunikasi dialogis yang intensif, ditemukan solusi terhadap berbagai persoalan yang dihadapi anak. Ketiga, komunikasi dialogis guru dan orangtua menghasilkan banyak temuan penting terkait perkembangan anak dan rekomendsi untuk pendampingan di masa mendatang.  Kata kunci: kreasi, eksplorasi, pengembangan diri, bakat